2009
DOI: 10.1111/j.1365-2621.2009.02036.x
|View full text |Cite
|
Sign up to set email alerts
|

Browning susceptibility of white wine and antioxidant effect of glutathione

Abstract: Glutathione (GSH) content and other physicochemical parameters of thirteen white wines originated from Lebanon were studied in relation to their browning capacity; the impact of pH, total sulphur dioxide and total phenol content into the browning susceptibility of the wine was shown. The effect of GSH, added to the wine at different concentrations, on the total phenol content was studied at 55°C during 8 days of accelerated oxidation. GSH addition resulted in significantly higher total phenol content only on d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 9 publications
6
38
1
Order By: Relevance
“…Thus, cold conditions permitted a better conservation of the initial lightness of the extracts. It is remarkable that, for both hue (h ab ) and lightness (L*), samples kept at 20°C for 12 days showed similarly values than those heated at 80°C in only 5 h. That fact evidenced that the color degradation of O. dillenii was accelerated by the thermal treatment, as affirmed (El Hosry, Auezova, Sakr, & Hajj-Moussa, 2009). …”
Section: Temperature and Colorimetric Characteristicsmentioning
confidence: 68%
“…Thus, cold conditions permitted a better conservation of the initial lightness of the extracts. It is remarkable that, for both hue (h ab ) and lightness (L*), samples kept at 20°C for 12 days showed similarly values than those heated at 80°C in only 5 h. That fact evidenced that the color degradation of O. dillenii was accelerated by the thermal treatment, as affirmed (El Hosry, Auezova, Sakr, & Hajj-Moussa, 2009). …”
Section: Temperature and Colorimetric Characteristicsmentioning
confidence: 68%
“…In fact, this effect has been previously observed in the study by Patel and collaborators (2010), in which a must added with a high content of GSH (67 mg L −1 ) decreased considerably its concentration until few milligrammes per litre after alcoholic fermentation. In spite of that, it has also been shown that wines from musts supplemented with GSH experienced slighter oxidation symptoms and exhibited better sensory characteristics than control wines (without GSH added to the must) (El Hosry et al 2009). Finally, the progressive reduction in reduced GSH observed during the shelf life of the wine (Fig.…”
Section: Idy Preparationmentioning
confidence: 97%
“…In this way the formation of o-quinones and, consequently, the production of browning polymers, is limited. GSH can thus have a positive effect on white wine colour, appearing to make the colour more stable during ageing (Hosry, Auezova, Sakr, & Hajj-Moussa, 2009;Lavigne & Dubourdieu, 2004;Vaimakis & Roussis, 1996).…”
Section: Introductionmentioning
confidence: 98%